013 Acute retinal detachment in retinopathy of prematurity (ROP-RD): UK national outcomes of endoscopic vitrectomy in 51 consecutive cases. (December 2018) - Wong, C; Yeo, D; Henderson, R; Patel, CK
Abstract : Introduction: ROP-RD can lead to bilateral blindness in a premature infant. Surgery is complex, necessitating sacrifice of the natural lens (lensectomy) of the eye in 57% with conventional surgical approaches with associated long-term ocular morbidity. Retinal re-attachment outcomes are variable. A novel surgical approach was developed at Great Ormond Street Hospital (GOSH) in 2014, combining endoscopic and microscope visualization during vitrectomy surgery. GOSH has since become the de facto UK national surgical centre. Purpose: To evaluate the efficacy and safety of endoscopic vitrectomy (Endo-Vit) for ROP-RD. Methods: This was a single centre, non-comparative consecutive case series of surgery for ROP-RD in ROP, between November 2014 and August 2017. Inclusion criteria were stage 4A or 4B ROP-RD. All cases had primary high-resolution 19-gauge endoscopy combined with conventional 23-gauge vitrectomy. Results: Fifty-one eyes of 35 patients were included. Mean gestational age, birth weight and follow-up were 26.0 weeks, 801 g and 4 months, respectively. ROP-RD stage was 4A in 24 eyes (47%), 4B in 21 eyes (41%) and 4B/5 in 6 eyes (12%). Forty-three eyes (84%) had prior laser treatment, and 16 eyes (31%) prior intravitreal bevacizumab. Median age at primary Endo-Vit was 44.7 weeks postmenstrual age. Median number of surgeries was 1. Bilateral simultaneous surgery was done in 16 patients (46%). Primary retinal re-attachment was 86% overall, 96% in stage 4A, 81% in stage 4B, and 67% in stage 4B/5. None required primary lensectomy. Intraoperative complications occurred in 4 eyes (8%), with 1 lens touch and 3 iatrogenic retinal breaks. Postoperative complications occurred in 2 eyes (4%), with 1 glaucoma and 1 treatment-requiring cataract. Conclusion: Endoscopic vitrectomy significantly reduces the need for primary lensectomy in high-risk ROP-RD compared to published outcomes (0% vs 57%), with favourable anatomic outcomes particularly with earlier intervention.